Ta có :
\(c=\frac{bd}{b-d}\Leftrightarrow bc-cd=bd\)
\(\Rightarrow bc=d\left(b+c\right)\)
\(\Rightarrow bc=ad\)
\(\Leftrightarrow\frac{a}{b}=\frac{c}{d}\)
Vậy ...
Ta có :
\(c=\frac{bd}{b-d}\Leftrightarrow bc-cd=bd\)
\(\Rightarrow bc=d\left(b+c\right)\)
\(\Rightarrow bc=ad\)
\(\Leftrightarrow\frac{a}{b}=\frac{c}{d}\)
Vậy ...
Cho a = b + c và \(c=\frac{b.d}{b-d}\) \(\left(b\ne0,d\ne0\right)\) Chứng minh: \(\frac{a}{b}=\frac{c}{d}\)
CHO \(a,b,c,d\ne0\)VÀ\(b^2=a.c;c^2=b.d;b^3+c^3+d^3\ne0\)
\(CMR:\frac{a^3+b^3+c^3}{b^3+c^3+d^3}=\frac{a}{d}\)
Cho a = b + c và c = \(\frac{bd}{b-d}\) \(b\ne0;d\ne0\)
Chứng minh rằng \(\frac{a}{b}=\frac{c}{d}\)
Cho a = b = c và \(c=\frac{bd}{b-d}\left(b\ne0;d\ne0\right)\)
Chứng minh \(\frac{a}{b}=\frac{c}{d}\)
cho \(b^2=a.c;c^2=b.d\) . với \(b,c,d\ne0;b+c\ne d;b^3+c^3\ne d^3\)
Chứng minh rằng
\(\frac{a^3+b^3-c^3}{b^3+c^3-d^3}=\left(\frac{a+b-c}{b+c-d}\right)^3\)
Chứng minh rằng từ tỉ lệ thức \(\frac{a}{b}=\frac{c}{d}\left(a-b\ne0,c-d\ne0\right)\) ta có thể suy ra tỉ lệ thức \(\frac{a+b}{a-b}=\frac{c+d}{c-d}\).
Chứng minh rằng từ tỉ lệ thức \(\frac{a}{b}=\frac{c}{d}\left(a-b\ne0,c-d\ne0\right)\)ta có thể suy ra tỉ lệ thức \(\frac{a+b}{a-b}=\frac{c+d}{c-d}\)
Chứng minh rằng từ tỉ lệ thức \(\frac{a}{b}=\frac{c}{d}\left(a-b\ne0,c-d\ne0\right)\)ta có thể suy ra tỉ lệ thức \(\frac{a+b}{a-b}=\frac{c+d}{c-d}.\)
cho\(\frac{a}{b}=\frac{c}{d}\) chưng minh rằng
\(\frac{a+b}{a-b}=\frac{c+d}{c-d}\) (với \(a-b\ne0,c-d\ne0\))